Are completed ReSPECT plans facilitating person-centred care? An evaluation of completed plans in UK general practice - Caroline J. Huxley; Karin Eli; Claire A. Hawkes; Frances Griffiths; Martin Underwood; Gavin D. Perkins; Hazel Blanchard; Jenny Harlock; Julia Walsh; Anne-Marie Slowther (Resuscitation Plus)
Background: The Recommended Summary Plan for Emergency Care and Treatment (ReSPECT) includes agreed clinical recommendations for a person’s care in a future emergency which have been informed by discussion of the person’s preferences. Previous evaluation of ReSPECT plans in acute NHS hospitals found inconsistencies in recording patient’s preferences and involvement in the plan, and infrequent justification for recommendations. Aim: To explore to what extent ReSPECT recommendations reflect individual preferences, as documented in the plan. Methods: ReSPECT plans of adults were collected from 11 General Practices in England. We adapted an evaluation tool used previously to analyse ReSPECT plans in acute settings. Free text sections for individual values/preferences and clinical recommendations were examined for clarity, consistency and congruency between them. Results: We retrieved 141 ReSPECT plans. Patients or those close to the patient were recorded as being consulted in most plans (94%). Individual preferences were completed in 57% of plans. Clinical recommendations reflected individual preferences by directly referencing the person and their preferences (31%), by being consistent with the documented preferences (30%), or by using the same wording as the preferences (6%). Conclusion: While many clinical recommendations reflect individual preferences, the preferences themselves are only recorded in just over half of ReSPECT plans. This is problematic, because the recording of individual preferences facilitates person-centred care, both directly by informing recommendations and indirectly when used to guide decision-making in situations not anticipated in the plan. Future training for clinicians should emphasize the need to document the personal values section of the plan.